ST. LOUIS ENCEPHALITIS : INFECTION OF CHICKEN MITES, DERMANYSSUS GALLINAE, BY FEEDING ON CHICKENS WITH VIREMIA; TRANSOVARIAN PASSAGE OF VIRUS INTO THE SECOND GENERATION - Smith, Margaret G. (The Rockefeller University Press, 1946)
A colony of chicken mites (Dermanyssus gallinae) was established from a single adult female mite and her offspring. This colony of mites was shown to be free of the virus of St. Louis encephalitis. Infection of mites from this homogeneous colony with the virus of St. Louis encephalitis was accomplished by feeding on chickens having viremia. The virus was recovered as readily from mites which had not been allowed to feed for 8 days as from mites freshly engorged, showing that the demonstration of virus in the mites does not depend on the presence of fresh infective chicken blood. Transovarian passage of the St. Louis virus into the second generation has been demonstrated in mites infected experimentally. The female mite infected as an adult can pass the St. Louis virus through eggs laid after additional feeding on normal blood. Persistence of the virus for a period of 6 months has been shown in a colony of mites infected experimentally in the laboratory.